Investigation on tritium retention and surface properties on the first wall in the large helical Device. (June 2021) - Yajima, M.; Masuzaki, S.; Yoshida, N.; Tokitani, M.; Otsuka, T.; Oya, Y.; Torikai, Y.; Motojima, G.; ,
Highlights: Examined tritium (T) retention in material probes on the first wall after the LHD 2017 campaign. Studied the relationships between surface microstructures and T retention in material probes. Much larger amounts of T remained in probes located at deposition-dominant area. Among probes located at erosion-dominant area, remaining T in the probe on which energetic tritons impinged was much larger than others. Abstract: In the Large Helical Device (LHD), the first deuterium plasma experiment was conducted in 2017. To investigate tritium migration in the LHD vacuum vessel, long-term material probes were installed on the first wall before the deuterium plasma experiment. After the experiment, the microstructure and amount of tritium remaining in each probe were analyzed. The results showed that a relatively large amount of tritium remained in the probes on the first wall, forming a thick deposition layer, rather than in the probes located in the erosion-dominant area. In the deposition layers on the probes, the dominant element is carbon, which can be generated on the divertor tiles made of graphite. The result of orbit calculation of the energetic tritons in the case of the standard magnetic configuration in the LHD showed that approximately 40% of the tritons generated by deuterium–deuterium fusion reactions were promptly lost mainly to the divertor. Thermalized tritons also flew to the divertor along with the background plasma. The divertor tiles, on which the tritons impinged, were eroded by the divertor plasma, and carbon atoms and tritiated hydrocarbon molecules were generated and deposited on the first wall. This can be the dominant mechanism of tritium retention in the first wall. Among the material probes located in the erosion-dominant area, the amount of tritium remaining in the probe on which the energetic tritons impinged was relatively large. The results of the tritium balance analysis show that the first wall is not the dominant reservoir of tritium in the LHD.